Rancang Bangun Alat Pemberi Pakan Ikan Menggunakan Mikrokontroler Pada Kolam Dengan Menjadwalkan Secara Teratur Memakai Energi Panel Surya - Mulyono, Arjun Bagus; Tukadi, Tukadi; Suryowinoto, Andy (Institut Teknologi Adhi Tama Surabaya, 2024)
In this era, there are many scientific technologies that make human work easier, including for developing businesses in the plantation, agriculture, livestock, and fisheries industries. However, Indonesia's natural resources have not been fully utilized due to several factors, such as a lack of human resources and inadequate technology. Much of the energy in this world has not been used optimally, such as the energy produced from sunlight that shines for about 12 hours a day. This sort of device is often called a solar panel or photovoltaic panel. It is a technological device to convert solar energy into electrical energy. Solar panels contain many solar cells made of semiconductor materials, such as silicon. They work based on photovoltaic effects, in which solar cells absorb sunlight and produce a flow of electrons to yield an electric current. Solar panels have become a popular and environmentally friendly source of renewable energy because they generate electricity without carbon emissions or air pollution. The use of solar panels has grown rapidly in recent years, including providing a voltage source for fish feeders to support the fishing business so that the costs incurred to care for fish are cheaper compared to manual feeding. The results of this project indicated that this fish-feeding system could feed 100 koi seeds twice a day, in the morning and evening at 8:00 WIB and 16:30 WIB. This tool was also equipped with a microcontroller, so that each time the feed opened for about 30 seconds, the pellet grain came out at approximately 100 grams. So, people can provide enough feed of 200 grams per day for 100 koi fish aged 2 months.